Spin-orbit torque induced magnetization switching in heavy metal/ferromagnet multilayers with bilayer of heavy metals. (August 2017) - Bekele, Zelalem Abebe; Meng, Kangkang; Zhao, Bing; Wu, Yong; Miao, Jun; Xu, Xiaoguang; Jiang, Yong
Abstract: Symmetry breaking provides new insight into the physics of spin-orbit torque (SOT) and the switching without a magnetic field could lead to significant impact. In this work, we demonstrate the robust zero-field SOT switching of a perpendicular ferromagnet (FM) layer where the symmetry is broken by a bilayer of heavy metals (HMs) with the strong spin-orbit coupling (SOC). We observed the change of coercivity value by 31% after inserting Co2 FeAl in the multilayer structure. These two HM layers (Ta and Pt) are used to strengthen the SOC by linear combination. With different angles between the magnetization and the current (i.e. parallel and anti-parallel), the structures show different switching behaviors such as clockwise or counterclockwise. Highlights: Spin-orbit coupling. Spin-orbit torque. Perpendicular Magnetic anisotropy. Spin polarized transport in metals. Spin transport effects.